Estimation and Forecasting of Evaporation Losses for Lake Mosul Dam - hussain, Elham abdulkreem; A. Mohamed, Dr.Nadera; N.S.Al-Shallawi, Dr.Ahmad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Evaporation from water bodies is important and considered a major problem in dry and semi-dry regions, in this research the evaporation has been analyzed from two approaches: engineeringly and statistically. The engineering approach deals with the calculation of evaporation rates of Mosul Dam Lake. Three methods were used: pan evaporation class A, the combined and the mass-transfer. It was found that the values ​​obtained by pan evaporation class A method was the highest among the other, while the mass transfer method achieved the lowest results. The evaporation rates during the year ranged according to the first method (0.9–5.5) mm/day, second (0.7–11.5) mm/day and the last method (1.0039×106) m3/year, which represents 9% of the highest storage in the Mosul Dam Lake.The statistical approach, the values ​​of the evaporation occurring in Mosul Dam Lake were forecasted for the 2016-2017 rainy period, and 255 observations were used to find two forecasting models that were constructed using the simple exponential smoothing and Holt methods, then compare the results with the actual values ​​of evaporation starting from (256 – 265) depending on MSE ,the Holt method gave less value to MSE than the simple exponential smoothing method, as its value was 0.421 versus 2.576. Matlab (14a) and R (3.2.1) were used in the statistical analysis.